The impact of COVID-19 Crisis on the Global Economy and the North American Hegemonic Cycle: A reading - Carvalho, Patrícia Nasser de (2020)
Based on the theorical framework that considers contextual and structural long-term perspectives of world hegemonic cycles and transitions of global powers, the aim of this reading is to critically analyze the ongoing and potential impact of the pandemic in the light of a conjunctural and historical perspective. The hypothesis is that although the COVID-19 crisis has already had deep negative impact on the global economy and represents a perfect storm for the US hegemony, seeing as the country is being challenged by many factors with strong magnitude and adverse effects, indeed it would not generate an immediate terminal crisis of the North American hegemony. Just in the long run the COVID-19 pandemic has the potential to trigger another world hegemonic power. The reading is based on the theoretical perspectives of world hegemonic cycles in international relations and is methodologically characterized as an explanatory and descriptive study and is built on a bibliographic review for the collection of theoretical and historical data.